2017
DOI: 10.1017/s0738248017000542
|View full text |Cite
|
Sign up to set email alerts
|

“On the other hand the accused is a woman…”: Women and the Death Penalty in Post-Independence Ireland

Abstract: Hannah Flynn was sentenced to death on February 27, 1924. She had been convicted of the murder of Margaret O'Sullivan, her former employer. Hannah worked for Margaret and her husband Daniel as a domestic servant, an arrangement that ended with bad feeling on both sides when Hannah was dismissed. On Easter Sunday, April 1, 1923, while Daniel was at church, Hannah returned to her former place of work, and killed 50-year-old Margaret with a hatchet. At her trial, the jury strongly recommended her to mercy, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…But: (a) most historic custodial abuses could be defined as crimes in the laws of the time; (b) various other factors meant they were ignored or defined away at the time, even by their victims, and (c) many of the latter are still alive and have received no redress. Considering the force of these points, we concur with others (e.g., [34,95,96]) that to suppress our moral emotions and refrain entirely from judgment would be unethical, colluding in the deflection of responsibility from those to whom it properly belongs.…”
Section: Research Materials and Methodssupporting
confidence: 80%
“…But: (a) most historic custodial abuses could be defined as crimes in the laws of the time; (b) various other factors meant they were ignored or defined away at the time, even by their victims, and (c) many of the latter are still alive and have received no redress. Considering the force of these points, we concur with others (e.g., [34,95,96]) that to suppress our moral emotions and refrain entirely from judgment would be unethical, colluding in the deflection of responsibility from those to whom it properly belongs.…”
Section: Research Materials and Methodssupporting
confidence: 80%
“…This was benign inclusivity for men who could be recovered to the traditional and acceptable settings of the family, the workplace and community. For convicted women, their double deviance often incurred a harsher patrician response, such as indefinite coercive confinement (Black, 2018). There was also the risk of unbridled discretion being more punitive, where people deemed bad simply would never be considered for release (Department of Justice, 1984a)—though this is an enduring problem of even the most regulated and bureaucratic parole systems and not limited to pastoral informality.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that women convicted of murder in this period in Ireland were considered first as women, and only secondly as murderers. 139 This is in stark contrast to the view of male violence from the late nineteenth century, which Martin Wiener cited as a focus for concern which conflicted with new models of masculinity. 140 In Ireland, the link between dangerousness and insanity was forged in the Dangerous Lunatics legislation of the nineteenth century.…”
Section: Dangerous or Difficult-gendered Understandings Of Insanitymentioning
confidence: 92%
“…144 This hierarchy of essential attributes meant that women were viewed as less dangerous than men who killed. 145 From the three case studies, it is evident that the women were viewed as 'difficult' rather than dangerous. In terms of 'perceptions of dangerousness', Prior found that patients in Dundrum who had previously been in prison were considered particularly troublesome.…”
Section: Dangerous or Difficult-gendered Understandings Of Insanitymentioning
confidence: 98%